2010
DOI: 10.1007/s00468-010-0423-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal variations in stem CO2 efflux of Pinus canariensis at their upper distribution limit

Abstract: We calculated stem CO 2 efflux (E S ) of Pinus canariensis at a timberline site in Tenerife, Canary Islands, from March 7, 2008 and February 9, 2009. E S varied markedly throughout the year. Although E S generally followed the seasonal trends in temperature, we observed seasonal adjustment of E S in both E S normalized to temperature (E S10 ) and the temperature sensitivity (Q 10 ) resulting in lower E S10 values during the warm and dry season as compared during the cold and wet season; the latter correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 53 publications
(103 reference statements)
1
17
1
2
Order By: Relevance
“…In conclusion, the stem CO 2 efflux increased with the temperature of the woody tissue, as many other studies have found (Teskey et al, 2008;Brito et al, 2010Brito et al, , 2013Yang et al, 2012). Thus, the stem CO 2 efflux increased according to the following series: winter, autumn, spring and summer.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In conclusion, the stem CO 2 efflux increased with the temperature of the woody tissue, as many other studies have found (Teskey et al, 2008;Brito et al, 2010Brito et al, , 2013Yang et al, 2012). Thus, the stem CO 2 efflux increased according to the following series: winter, autumn, spring and summer.…”
Section: Discussionsupporting
confidence: 60%
“…Because most transpiration occurs during the day, the stem CO 2 efflux is expected to be lower during the day than at night (Martin et al, 1994;Maier and Clinton, 2006;Teskey et al, 2008;Höltta andKolari, 2009: Gruber et al, 2009;Brito et al, 2010). Alternative explanations include the possibility that (i) the temperatures measured a short distance beneath or at the surface of the bark, as in this study, may not be representative of the temperatures experienced by most of the respiring biomass (Derby and Gates, 1966); (ii) some CO 2 is stored temporarily (Höltta and Kolari, 2009); and (iii) stem respiration depends also on plant water stress (Lavigne, 1987;Teskey et al, 2008;Saveyn et al, 2007), which might be more severe during the day than during the night.…”
Section: Discussionmentioning
confidence: 99%
“…These include: (1) long radial diffusion pathways of CO 2 and high bark resistance to gaseous diffusion (Stockfors 2000;Ceschia et al 2002), (2) CO 2 absorption and transport in the transpiration stream (Teskey and McGuire 2002;Saveyn et al 2007a), (3) corticular photosynthesis, especially important for young stems and branches (Sprugel 1990;Cernusak and Marshall 2000;Wittmann et al 2001Wittmann et al , 2006Pfanz 2007, 2008), (4) cambial activity, substrate supply and growth (Martin et al 1994;Stockfors and Linder 1998;Damesin et al 2002), and (5) other environmental and physiological factors that either directly or indirectly affect E S including sap flow, phenology, stem oxygen concentration, substrate supply, solar radiation, and water deficits Bowman et al 2005;Saveyn et al 2007b;Meir et al 2008;Zach et al 2010;Gruber et al 2009;Aubrey and Teskey 2009;Brito et al 2010;Maier et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…树干CO 2 释放通量(E s )占树木自养呼吸的15%-45% (Ryan et al, 1994;Maier et al, 2004;肖复明等, 2005), 是树木和森林生态系统年碳平衡的重要组 分 。 E s 能 消 耗 森 林 生 态 系 统 总 初 级 生 产 力 的 8%-13%, 对森林生产力有重要的影响 (Ryan et al, 1994;Maier et al, 2004;Zha et al, 2004) (Zha et al, 2004;Cavaleri et al, 2006;Brito et al, 2010;Araki et al, 2015)。绝大多数温带 和北方森林树木E s 的经典季节变化模式为: 在温度 高、树干生长快速的夏季达到高峰值, 在低温、树 干生长停止的秋冬季减小到最小值 (Lavigne & Ryan, 1997;Zha et al, 2004;Gruber et al, 2009;Yang et al, 2012a); 相反, 处于终年温暖、树干全年生长的热带 地区树木的E s 的季节动态格局更加复杂化, 比如干 旱季节的E s 低于 (严玉平等, 2008;Stahl et al, 2011) 或高于 (Zach et al, 2010) (Zha et al, 2004;Brito et al, 2010;Araki et al, 2015)。此外, 底物供应 (Maier et al, 2010)、形成层活动 (Gruber et al, 2009)、树干生 长 (Brito et al, 2010;Araki et al, 2015)、边材氮浓度 (Maier, 2001;孙涛等, 2015) (Cavaleri et al, 2006)和生 长节律、液流速度 (Katayama et al, 2016)、底物供应 (Zach et al, 2010)、土壤含水量 (Stahl et al, 2011)等 生物或非生物因子才是主导该区域E s 季节变化的主 要因素。另外, 虽然目前有许多研究指出同一树种 内不同树木个体间和同一树木个体内不同部位间的 E s 存在很大差异 (Ceschia et al, 2002;Bowman et al, 2005;Yang et al, 2012b) 王淼等, 2008;石新立等, 2010;王秀伟等, 2011;许飞等, 2011;Yang et al, 2012a;孙涛等, 2015 …”
unclassified
“…(Gruber et al, 2009)或者无影响 (Brito et al, 2010;Araki et al, 2015) Steppe et al, 2007), Maier et al, 1998;Stockfors & Linder, 1998 et al, 1994;Brito et al, 2010;Yang et al, 2012b …”
unclassified